2003
DOI: 10.1074/jbc.m305964200
|View full text |Cite
|
Sign up to set email alerts
|

Akt-mediated Cardiomyocyte Survival Pathways Are Compromised by Gαq-induced Phosphoinositide 4,5-Bisphosphate Depletion

Abstract: Expression of the wild type ␣ subunit of G q (G q WT) in cardiomyocytes induces hypertrophy, whereas a constitutively active G␣ q subunit (G q Q209L) induces apoptosis. Akt phosphorylation increases with G q WT expression but is markedly attenuated in cardiomyocytes expressing G q Q209L or in those expressing G q WT and treated with agonist. A membrane-targeted Akt rescues G q Q209L-expressing cardiomyocytes from apoptotic cell death. In contrast, leukemia inhibitory factor fails to activate Akt or promote cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 48 publications
1
50
1
Order By: Relevance
“…As we have previously reported (15), constitutively activated Akt (myr-Akt) rescues cells from apoptosis induced by Q209L expression (Fig. 8A).…”
Section: Cytosolic Camentioning
confidence: 64%
See 2 more Smart Citations
“…As we have previously reported (15), constitutively activated Akt (myr-Akt) rescues cells from apoptosis induced by Q209L expression (Fig. 8A).…”
Section: Cytosolic Camentioning
confidence: 64%
“…We also reported that constitutively activated Akt inhibits development of apoptosis in this system (15). Neither the mechanisms underlying induction of the PT-pore nor the mechanisms of Akt-mediated protection have been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was shown that the activation of Gq-coupled M1, M3, and M5 muscarinic receptors but not Gi-coupled M2 and M4 receptors could protect cells from apoptosis induced by etoposide or UV (20,23,24). Other reports suggest instead that signaling of Gq, either activated by a GPCR or in the form of a constitutively active mutant (CAM), can inhibit the activation of Akt induced by growth factors and trigger apoptosis (25)(26)(27)(28)(29). Additional studies showed an opposite effect for Gqcoupled receptors (phosphorylation of Akt and inhibition of apoptosis) and CAMs of Gq (reduction of phosphorylation of Akt and apoptosis; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Similar pathways could also play important roles in retinal degeneration associated with mutations in PI recycling genes, such as rdgB, cds, rdgA and dpis. Interestingly, PtdIns(4,5)P 2 depletion mediated via effects of RhoA on PtdIns(4)P5-kinase has been implicated in cardiac hypertrophy (Howes et al, 2003;Miyamoto et al, 2010). Cardiomyocytes are also known to express high levels of TRP channels which play important roles in their functioning and maintenance (Vennekens, 2011;Watanabe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%